WO3 Nanofiber‐Based Biomarker Detectors Enabled by Protein‐Encapsulated Catalyst Self‐Assembled on Polystyrene Colloid Templates. Issue 7 (5th January 2016) - Choi, Seon‐Jin; Kim, Sang‐Joon; Cho, Hee‐Jin; Jang, Ji‐Soo; Lin, Yi‐Min; Tuller, Harry L.; Rutledge, Gregory C.; Kim, Il‐Doo
Abstract : A novel catalyst functionalization method, based on protein‐encapsulated metallic nanoparticles (NPs) and their self‐assembly on polystyrene (PS) colloid templates, is used to form catalyst‐loaded porous WO3 nanofibers (NFs). The metallic NPs, composed of Au, Pd, or Pt, are encapsulated within a protein cage, i.e., apoferritin, to form unagglomerated monodispersed particles with diameters of less than 5 nm. The catalytic NPs maintain their nanoscale size, even following high‐temperature heat‐treatment during synthesis, which is attributed to the discrete self‐assembly of NPs on PS colloid templates. In addition, the PS templates generate open pores on the electrospun WO3 NFs, facilitating gas molecule transport into the sensing layers and promoting active surface reactions. As a result, the Au and Pd NP‐loaded porous WO3 NFs show superior sensitivity toward hydrogen sulfide, as evidenced by responses ( R air / R gas ) of 11.1 and 43.5 at 350 °C, respectively. These responses represent 1.8‐ and 7.1‐fold improvements compared to that of dense WO3 NFs ( R air / R gas = 6.1). Moreover, Pt NP‐loaded porous WO3 NFs exhibit high acetone sensitivity with response of 28.9. These results demonstrate a novel catalyst loading method, in which small NPs are well‐dispersed within the pores of WO3 NFs, that is applicable to high sensitivity breath sensors. Abstract : A novel catalyst functionalization method is proposed using self‐assembly of protein‐encapsulated catalytic nanoparticles on polystyrene colloid templates. These templates are employed in electrospinning to achieve well‐dispersed catalyst functionalization and form open pores on the semiconductor metal oxide nanofibers (NFs) after subsequent heat‐treatment. The improved analyte sensing performance is investigated with catalyst‐loaded porous WO3 NFs.